The Effect of Coconut Shell Liquid Smoke Concentration on the Sensory Characteristics and Total Bacterial Count of Catfish Meatballs Substituted with Oyster Mushrooms During Storage - Anindita Wahyu Noer Anggraini; Ratna Yulistiani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study aimed to determine the effect of coconut shell liquid smoke concentration on the sensory characteristics at Day 0 and the total bacterial count during storage of catfish meatballs substituted with oyster mushrooms. A completely randomized design was used with treatments of 0.5%, 1%, 1.5%, and 2% (v/v) coconut shell liquid smoke. Sensory evaluation was conducted at Day 0 using a hedonic scale with 30 semi-trained panelists who evaluated color, aroma, taste, and texture. Sensory data were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test (DMRT) at a 5% significance level. The treatment with the best sensory characteristics was selected using the De Garmo Effectiveness Index and subsequently evaluated for total bacterial count during 12 days of storage at 6°C and 30°C. The best treatment was 1.5% coconut shell liquid smoke, with sensory scores of 4.43 (somewhat like) for color, 4.90 (like) for aroma, 5.30 (like) for taste, and 4.83 (like) for texture. At 30°C, total bacterial count increased from a baseline of 3.70 log CFU/g to 7.30 log CFU/g on Day 4, remained at 7.30 log CFU/g on Day 8, and reached 8.10 log CFU/g on Day 12. At 6°C, total bacterial count increased from 3.70 log CFU/g to 4.42 log CFU/g, 4.67 log CFU/g, and 5.19 log CFU/g on Days 4, 8, and 12. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production